Humidität und Kulturpflanzen - Ein Versuch zur Parallelisierung von Feuchtezonen und optimalen Standorten ausgewählter Kulturpflanzen in den Tropen - Schmiedecken, Wolfgang (ERDKUNDE, 1979)
Observations of water budget provide the potential (pLV) and the actual (aLV) regional evaporation, with the quotient of both of them (aLV/pLV) - in conformity with the subject matter - indicating the aridity limit at 1.0. The differentiation as to totally arid, semi-arid, semi-humid and totally humid months, the duration of the humidity situation of the time and the collation in a four figure reference number permit the setting up of an uninterrupted model of up to 455 different humidity zones. In the case of sorghum and groundnut, two tropical cultivated plants, it is shown that the values which were found for the actual evaporation of the region are to be parallelized with those of the transpiration of the plants in question. The conversion of these results to the aLV/pLV quotients and thus to the humidity zones leads to an unambiguous correlation, which in turn permits the definition of optimal potential areas of cultivation.